Evaluation of knowledge and behavior of nurses working in intensive care units for endotracheal aspiration application - Bozan, Safure; Güven, Şefika Dilek (Journal of Surgery and Medicine, 2020)
Aim: Endotracheal aspiration is one of the most common invasive procedures administered by intensive care nurses in patients receiving mechanical ventilation to provide and maintain adequate oxygenation, alveolar ventilation, and gas exchange, prevent pulmonary consolidation and atelectasis, and reduce the risk of ventilator-associated pneumonia. When the endotracheal aspiration procedure is not administered correctly, the patient may have serious complications such as arterial and venous desaturation, cardiac arrhythmia, cardiac arrest, atelectasis, bronchospasm, lower respiratory tract contamination, ventilator-induced pneumonia, anxiety, and dyspnea. The study aims to evaluate the knowledge and behaviors of nurses working in intensive care units for endotracheal aspiration applications. Methods: This study used a cross-sectional and descriptive design including a questionnaire-based nurse survey. It was conducted between 17 March 2015-30 June 2015 with 54 nurses working in intensive care units in a public hospital. In the study, the data were collected with a questionnaire, endotracheal aspiration information form, and nurse observation form for endotracheal aspiration. The evaluation of the data was conducted using numbers and percentages. The ethics committee approval, institutional permission, and participant consent were obtained before starting the research. Results: It was determined that the nurses participating in the study were incompetent before, during, and after the endotracheal aspiration procedure and that they did not have sufficient information about endotracheal aspiration. Conclusion: In line with the results of the study, it was suggested that the nurses should be trained on endotracheal aspiration, the effect of education on practice should be evaluated, and that standardization studies should be carried out to minimize deficient and erroneous practices in endotracheal aspiration.